FOMC news and segmented markets - Golez, Benjamin; Kelly, Peter; Matthies, Ben (Journal of Accounting and Economics, 2025)
A growing body of evidence suggests that Federal Open Market Committee (FOMC) announcements can affect private sector beliefs about near-term macroeconomic conditions. We measure the impact of central bank policy on index option trader beliefs about near-term economic conditions using the return of short-term dividend strips around each FOMC announcement (we term this short-term dividend strip return, “SDR”). Consistent with the idea that these announcements contain valuable information about macroeconomic conditions, we find that SDR predicts both future firm-level earnings and firm-level earnings announcement returns. Furthermore, using analyst earnings forecasts, we provide evidence of belief underreaction to FOMC announcements. We discuss how investor specialization and segmented markets can generate our empirical results.